Disentangling the role of income level on premium brand perceived quality, awareness, association, and loyalty: A comparative study within Thailand and Indonesia - Pechinthorn, Komm; Irawan, Nico; Thant Zin, Kyawt Shinn; Suasungnern, Sineenat; Samarkjarn, Jirangrug; Rahmawati, Rahmawati (University of Islam Malang, 2021)
The level of income is one of the specific consumer conditions that susceptible to influence their brand decision-making. Unfortunately, studies on the influence of income mainly focused on price without considering the relationship between brand and consumers. This study aims to examine how brand perceived quality, awareness, association, and loyalty related to the level of income in emerging countries like Thailand and Indonesia. Premium and high-class coffee chain brands choose as the object of this study as the exponential growth of the coffee culture in both countries. A total of 283 respondents have completed an online questionnaire and verified it to be processed into the analysis of variance (ANOVA) and LSD post hoc test for multiple comparison statistical analysis. The result of this study shows that although high-income and low-income consumers in Thailand tend to have the same perceived quality toward the premium coffee brand, in general, there is a significant difference in the mean of brand perceived quality, awareness, and association between various consumers income level in Thailand. Interestingly, this study found that there is no significant difference in the mean of premium coffee brand perceived quality, awareness, association, and loyalty within the group of income levels in Indonesia. This indicates that Indonesians tend to ignore how much money they have in their pocket when it comes to coffee as the coffee culture becoming a new habit and lifestyle.